2015
DOI: 10.4081/or.2015.6046
|View full text |Cite
|
Sign up to set email alerts
|

Lower back pain with sciatic disorder following L5 dermatome caused by herpes zoster infection

Abstract: We report the case of a 62-year-old patient with lower back pain radiating into the right leg accompanied by numbness. The pain had an acute onset and was resistant to conservative pain treatment. A magnetic resonance imaging (MRI) scan of the lumbar spine showed no degenerative discovertebral lesions, but a swelling of the nerve root supplying the affected dermatome. For pain treatment the patient received lumbar epidural infiltrations. During this treatment the patient suddenly developed a skin rash with gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…It has been hypothesised that local inflammation of the dorsal root ganglion results in hypervascularity in the surrounding nerve tissue, disrupting the blood-nerve barrier which can also result in a motor deficit. 3 Therefore, although postherpetic neuralgia is a common manifestation of herpes zoster infection, segmental zoster paresis is rare. Although reported incidences in different countries vary, a recent study performed with a majority of Chinese patients reported paresis in only 0.57% of those afflicted with a zoster infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesised that local inflammation of the dorsal root ganglion results in hypervascularity in the surrounding nerve tissue, disrupting the blood-nerve barrier which can also result in a motor deficit. 3 Therefore, although postherpetic neuralgia is a common manifestation of herpes zoster infection, segmental zoster paresis is rare. Although reported incidences in different countries vary, a recent study performed with a majority of Chinese patients reported paresis in only 0.57% of those afflicted with a zoster infection.…”
Section: Discussionmentioning
confidence: 99%
“…A plain magnetic resonance imaging can exclude the presence of nerve root impingement, although findings that may suggest zoster infection such as spinal nerve swelling with T2 hyperintensity are neither sensitive nor specific. 3 The mainstay of treatment for zoster radiculopathy is pharmacological. A course of antivirals is prescribed for the acute herpetic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hackenberg et al . [ 12 ] reported a 62-year-old patient with lower back pain radiating into the right leg. MRI showed no degenerative lesions, but swelling of nerve root supplying the affected dermatome.…”
Section: Discussionmentioning
confidence: 99%
“…Though relatively rare, the virus can affect the corresponding myotome and cause motor weakness or paresis after VZV reactivation [ 4 - 6 ]. If the virus affects the lower motor nerve, the symptom may mimic sciatica or paresis caused by the lumbar spine lesion [ 7 - 10 ]. Moreover, the weakness or paresis can infrequently occur in the absence of the typical skin lesion associated with herpes zoster and make it extremely difficult to diagnose [ 11 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Favorable prognosis of herpes zoster-associated motor paresis has been generally reported [ 7 , 9 - 10 ], while prolonged weakness may happen [ 6 , 13 , 15 ]. The prognostic factor is still unclear yet, but the risk of the persisting symptom may get higher if treatment is delayed [ 17 ].…”
Section: Discussionmentioning
confidence: 99%